‘Tinder’ and the Rise of Hook-Up Culture: Mapping an Islamic Solution - Ahmad Shidqi Mukhtasor (Journal of Comparative Study of Religions (JCSR), 2022)
The current understanding of sex has deviated from the normative values of Islam, where sexual activity outside of marriage has increased sharply. This is due to the emergence of a new sex culture called the 'hook-up culture', where a person engages in casual sex with the aim of fulfilling his own pleasure without any commitment. The development of the digital era has contributed to the growth of the hook-up culture and has become more real in modern human life. More specifically, after the presence of one of the most prominent dating applications, Tinder. This phenomenon shows the decline of human civilization. Whereas Islam as a religion of civilization describes sex as an element that forms human dignity and contributes to the formation of a quality civilization. This article tries to find a new conceptual framework in solving the problem of hook-up culture through an Islamic perspective. The research in this article explores the relationship between Tinder and hook-up culture and suggests Islam as a solution. The findings of this study indicate that the resolution that the ummah currently has in solving the problem of hook-up culture is still very specific in the discipline of Islamic studies, and needs further integration to overcome the problem of hook-up culture in society through exploring the key concepts of Islam and practical updates.